Programming in Python 3 : A complete introduction to the python language - Mark Summerfield (Uttar Pradesh Pearson India education services Pvt Ltd, 2025)
A Fully Revised Edition Featuring New Material on Coroutines,Debugging,Testing,Parsing,String Formatting,and More Python 3 is the best version of the language yet: It is more powerful,convenient,consistent,and expressive than ever before. Now,leading Python programmer Mark Summerfield demonstrates how to write code that takes full advantage of Python 3's features and idioms. Programming in Python 3,Second Edition,brings together all the knowledge you need to write any program,use any standard or third-party Python 3 library,and create New library modules of your own.Summerfield draws on his many years of Python experience to share deep insights into Python 3 development you won't find anywhere else. Chapter 1: Rapid Introduction to Procedural Programming Chapter 2: Data Types Chapter 3: Collection Data Types Chapter 4: Control Structures and Functions Chapter 5: Modules Chapter 6: Object-Oriented Programming Chapter 7: File Handling Chapter 8: Advanced Programming Techniques Chapter 9: Debugging, Testing, and Profiling Chapter 10: Processes and Threading Chapter 11: Networking Chapter 12: Database Programming Chapter 13: Regular Expressions Chapter 14: Introduction to Parsing Chapter 15: Introduction to GUI Programming
Keywords: python 3